Pancasila sebagai paradigma pendidikan karakter membentuk generasi unggul dan berintegritas - Aprila, Najwa Tabina Raihanun (Maliki Interdisciplinary Journal, 2025)
Pancasila is an open ideology that refers to a collection of doctrines and ideas embraced by the Indonesian people. Its main specialty is its open and flexible nature, which allows its basic values ​​​​to remain strong, but its application can adapt to the times, modernization, and societal changes without losing its original meaning. As a paradigm, Pancasila functions as a framework for thinking, foundation, and the main benchmark for all aspects of national and state life, ensuring that development is always oriented towards divinity, just humanity, deliberative democracy, and the realization of social justice. In the context of character education, Pancasila places five principles as a moral compass that guides students to become people who are faithful and pious, just and civilized, love their homeland and are united, democratic and respect deliberation, and care for and strive to realize social justice. Specifically, the implementation of Pancasila values ​​​​can develop a generation that has high superior and upholds moral principles and integrity. This character building focuses on five important elements: Religiousness, Nationalism, Independence, Mutual Cooperation, and Integrity, which are expected to provide reinforcement in the national education system so that the substance of Pancasila can be realized, thus producing a generation that is responsible and ready to maintain the integrity and progress of the nation.